Predictors of blood pressure control in an urban primary care setting. Issue 6 (November 2005) - Salifu, Moro O; Haria, Dhiren M; Ujire, Manasa; Aytug, Serhat; Ewaleifoh, Benedict; Bankole, Olusegun; Hayat, Amir; Delano, Barbara G; McFarlane, Samy I
Background: Despite evidence of decreased cardiovascular disease morbidity and mortality, control of blood pressure is largely suboptimal especially in urban settings. Evaluation of predictors of blood pressure control in these settings is exceedingly important in order to develop strategies for improved outcomes.Methods: We surveyed 259 African––American patients with essential hypertension in an urban primary care setting. Patients were divided into two groups, based on whether blood pressure was controlled, below 140/90 mmHg (n  =  181; 70%) or uncontrolled, above 140/90 mmHg (n  =  78; 30%). Predictors of blood pressure control were determined using multivariable logistic regression.Results: There were no differences between the two groups in mean age, body mass index or gender. Controlled as compared with uncontrolled patients had a significantly higher percentage of reporting regular exercise (p = 0.01), lower rate of blood pressure medication nonadherence (p  =  0.03), were less likely to be prescribed calcium channel blockers (p  =  0.01), lower rate of total serum cholesterol (<240  mg/dl; p  = 0.03) and lower serum creatinine (p = 0.04). All other factors were similar between the two groups. The odds ratio (OR) of uncontrolled blood pressure was associated with lack of regular exercise (OR: 2.26; 95% confidence interval [CI]: 1.16––4.37; p  =  0.02), use of calcium channel blockers (OR 2.30; 95% CI: 1.22––4.32; p = 0.01), total cholesterol greater than 240  mg/dl (OR: 3.10; 95%  CI: 1.36––7.00; p = 0.01), and blood pressure medication nonadherence (OR: 1.96; 95%  CI: 1.02––3.74; p  =  0.01).Conclusion: These data form a basis, and indicate the need for focused interventions to control blood pressure in urban primary care settings.